Economics of Information Security and Privacy III 2012
DOI: 10.1007/978-1-4614-1981-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Real Name Verification Law on the Internet: A Poison or Cure for Privacy?

Abstract: As the internet media has become more widely used over time, public opinions formed by internet discussions affect political and social issues more critically. While the internet space guarantees equal status for every participant and equal opportunity in terms of freedom of speech based on anonymity, baseless rumors, personal defamation, and privacy invasion against particular individuals and groups are more likely to happen rather than in the face-to-face offline communications. In order to prevent this unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Moreover, the study also indicated that the RNS had reduced negative behaviors, resulting in fewer swear words and 􀅫laming posts. This suggests that the law has encouraged users to behave well (Cho, 2013). Cho, Kim, and Acquisti (2012) did extensive research, in which the decrease in negative posts was seen after the implementation of RNS.…”
Section: Identity Veri􀅮icationmentioning
confidence: 99%
“…Moreover, the study also indicated that the RNS had reduced negative behaviors, resulting in fewer swear words and 􀅫laming posts. This suggests that the law has encouraged users to behave well (Cho, 2013). Cho, Kim, and Acquisti (2012) did extensive research, in which the decrease in negative posts was seen after the implementation of RNS.…”
Section: Identity Veri􀅮icationmentioning
confidence: 99%
“…However, this does not solve the issue as once non‐face‐to‐face interactions occur, there is only limited information available regarding the person receiving the service. There have been some attempts to develop national compulsory online identities in South Korea (Cho, ) but these have not succeeded. Future Apps developed specifically for telepsychology may include restricting the psychological services to specific Internet Protocol addresses or International Mobile Equipment Identity numbers which were used in the identity verification process.…”
Section: Competence In the Use Of Internet Communication Technologiesmentioning
confidence: 99%
“…But it's not embrace by all [12,13]. The doubt mostly originates from the threat of privacy leaking.…”
Section: Related Workmentioning
confidence: 99%